Analysis Assessment, Training and Counseling on Employee Performance is Mediated by Job Satisfaction at Cargo Companies - Primadi Candra Susanto; Aswanti Setyawati; Cecep Pahrudin; Sugiyanto Sugiyanto; Esterlinus Edwin Lermatan; Euis Saribanon; Sarinah Sihombing (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the effects of assessment, training, mentoring, and counseling on employee performance, with job satisfaction as a mediating variable, in sea cargo expedition companies in Jakarta. A descriptive quantitative approach was used, with data collected through a Likert-scale questionnaire (1–5) from 88 respondents selected using a census technique. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method via SmartPLS version 4.1.0.0. The results show that assessment and training have a positive and significant effect on job satisfaction, while mentoring and counseling have no significant effect. Assessment also has a direct and significant effect on employee performance, whereas training, mentoring, and counseling do not. Job satisfaction is found to significantly mediate the relationship between assessment and employee performance. These findings highlight the importance of effective assessment practices in enhancing job satisfaction and employee performance, while suggesting the need to improve the implementation of training, mentoring, and counseling programs.   Keywords: Employee Performance, Job Satisfaction, Assessment, Training, Counseling